Alterations of lung microbiota in patients with non-small cell lung cancer. Issue 3 (1st March 2022) - Zeng, Wen; Zhao, ChengZhu; Yu, Mengge; Chen, Hailong; Pan, Yiyun; Wang, Yuhuan; Bao, Hejing; Ma, Hao; Ma, Shudong
ABSTRACT: The role of lung microbiota in non-small cell lung cancer remains unclear. We investigated the characteristics and functional roles of lung microbiota in non-small cell lung cancer. Bronchoalveolar lavage fluid samples were obtained from patients with non-small cell lung cancer (n = 46) and with benign lung disease (n = 29). The differences in composition and gene expression in the microbiota between the samples were analyzed using 16s rRNA sequencing. The oncogenic genus ( Veillonella ) was then evaluated in the progression of lung cancer in C57 BL/6 mice. Compared to benign lung disease, the lung microbiota in non-small cell lung cancer was significantly altered, both in terms of α- and β-diversity. In terms of bacterial composition, the non-small cell lung cancer group was enriched with two Phyla (Firmicutes, Bacteroidetes) and three genera ( Streptococcus, Prevotella, Veillonella ). Prevotella and Veillonella were most strongly associated with non-small cell lung cancer, and Veillonella significantly promoted the progression of lung cancer in vivo . Moreover, metabolic prediction revealed that ribosomes, biosynthesis of secondary metabolites, and pyrimidine metabolism were among the enriched pathways that may be involved in the progression of non-small cell lung cancer. Overall, results suggest that the progression of non-small cell lung cancer is followed by significant changes in the composition and function of the lung microbiota. These differing genera may be potential diagnostic markers and therapeutic targets. Graphical abstract: uf0001